Implementation of Individual Counseling Service Management with Directive Counseling Methods in Improving Self-Adjustment - Saiful Akhyar Lubis; Sunan Aswin; Abdul Aziz Rusman (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article aims to find out the application of individual counseling services with directive counseling methods in increasing the adjustment of MAS Al washliyah students. Self-adjustment is one of the most important things when students enter a new school environment. One method in individual counseling is the directive counseling method. The counseling directive is one of the techniques or methods in which the counselor has a more dominant role and actively provides direction in accordance with the needs of the client. Directive counseling is a step that can be done in an effort to improve the adjustment of students who experience low adjustment due to differences in mood and learning climate from previous schools such as anxiety and fear of entering a new environment. This research uses descriptive qualitative research, the research informant is a BK teacher and 5 students. Data collection techniques are interviews, observations, and documentation studies. While data collection tools are interview guidelines, documentation study observation guides. The results of this study showed that counseling individuals with directive counseling methods can improve student self-adjustment. This is evident from the optimistic attitude of students and changes in interaction with the environment.